Sealing sheet

A laminated sealing sheet with a peelable moisture-proof layer addresses the inefficiencies in drying and contamination issues of resin composition layers, ensuring effective protection for electronic devices.

JP7616065B2Active Publication Date: 2025-01-17AJINOMOTO CO INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021556163
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-13
Filing Date
2020-11-13
Publication Date
2025-01-17
Estimated Expiration
2040-11-13

AI Technical Summary

Technical Problem

Existing sealing sheets with moisture-proof films on both sides of a resin composition layer fail to efficiently dry the resin composition layer and can lead to contamination during drying.

Method used

A laminated sealing sheet structure comprising a first moisture-proof sheet, a resin composition layer, and a second non-moisture-proof sheet that can be peeled off, with a third moisture-proof sheet, allowing efficient drying of the resin composition layer while preventing contamination.

Benefits of technology

The laminated structure enables efficient drying of the resin composition layer and prevents contamination, maintaining the integrity of the sealing sheet for electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616065000001
    Figure 0007616065000001
  • Figure 0007616065000002
    Figure 0007616065000002
  • Figure 0007616065000003
    Figure 0007616065000003
Patent Text Reader

Abstract

The present invention provides a sealing sheet having a laminated structure including a first sheet, a resin composition layer, a second sheet, and a third sheet, in this order. The water vapor transmission rates of the first sheet and the third sheet are each independently 1 (g / m2 / 24 hr) or less, and the water vapor transmission rate of the second sheet is 10 (g / m2 / 24 hr) or more. In addition, the third sheet can be detached.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an encapsulating sheet useful for encapsulating electronic devices. [Background technology]

[0002] Electronic devices such as organic electroluminescence (EL) devices and solar cells are vulnerable to moisture, and have problems such as a decrease in brightness and efficiency due to moisture. In order to protect the electronic devices, elements are encapsulated using an encapsulating sheet having a resin composition.

[0003] A sealing sheet having a resin composition layer containing moisture cannot adequately protect an electronic device. Therefore, Patent Document 1 proposes a sealing sheet having a first moisture-proof film, a resin composition layer, and a second moisture-proof film in order to suppress moisture absorption of the resin composition layer during storage. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 181426 Summary of the Invention [Problem to be solved by the invention]

[0005] In a sealing sheet having a structure in which moisture-proof films are provided on both sides of a resin composition layer as described in Patent Document 1, the moisture-proof films prevent the removal of moisture from the resin composition layer, so the resin composition layer cannot be dried efficiently. In addition, when the sheet with the exposed resin composition layer is dried after the second moisture-proof film is peeled off from the sealing sheet, the resin composition layer may be contaminated during drying.

[0006] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a sheet for sealing that can efficiently dry a resin composition layer and prevent contamination of the resin composition layer during the drying. [Means for solving the problem]

[0007] The present invention capable of achieving the above object is as follows. [1] A sheet for encapsulation having a laminated structure including a first sheet, a resin composition layer, a second sheet, and a third sheet in this order, The water vapor permeability of the first sheet and the third sheet is independently 5 (g / m 2 / 24hr) or less, The water vapor permeability of the second sheet is 10(g / m 2 / 24hr) or more, and The sealing sheet from which the third sheet can be peeled off. [2] The sealing sheet according to [1] above, wherein a 90-degree peel strength between the second sheet and the third sheet is 0.1 gf / inch or more and 250 gf / inch or less. [3] The sealing sheet according to [1] or [2], wherein the third sheet is a sheet having an adhesive layer, and the adhesive layer is in contact with the second sheet. [4] The encapsulating sheet according to any one of the above [1] to [3], wherein the second sheet has a release layer, and the release layer is in contact with the resin composition layer. [5] The encapsulating sheet according to any one of the above [1] to [4], wherein the first sheet has a release layer, and the release layer is in contact with the resin composition layer. [6] The sealing sheet according to any one of the above [1] to [5], wherein the resin composition layer contains semi-calcined hydrotalcite. [7] The encapsulating sheet according to any one of the above [1] to [6], which is a sheet used for encapsulating an electronic device. [8] The encapsulating sheet according to the above [7], wherein the electronic device is an organic electroluminescence device, a quantum dot device or a solar cell. Effect of the Invention

[0008] The encapsulating sheet of the present invention can efficiently dry the resin composition layer and can prevent contamination of the resin composition layer during the drying. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The encapsulating sheet of the present invention has a laminated structure including a first sheet, a resin composition layer, a second sheet, and a third sheet in this order.

[0010] In the present invention, the water vapor transmission rate (hereinafter sometimes abbreviated as "WVTR") of the first sheet and the third sheet is independently 5 (g / m 2 / 24hr) or less, that is, the first sheet and the third sheet are moisture-proof sheets. Also, the present invention is characterized in that the water vapor permeability of the second sheet is 10 (g / m 2 / 24 hr) or more, that is, the second sheet is a non-moisture-proof sheet. Another feature of the present invention is that the third sheet can be peeled off.

[0011] The sealing sheet of the present invention having the above-mentioned configuration can efficiently dry the resin composition layer in a state where the moisture-proof third sheet is peeled off before drying and the resin composition layer is protected by the non-moisture-proof second sheet. After drying of the resin composition layer, the peeled third sheet or a new third sheet may be laminated on the second sheet.

[0012] The first sheet, the second sheet and the third sheet may each have a single-layer structure or a laminated structure, preferably a laminated structure. The first sheet and the third sheet, which are moisture-proof sheets, are more preferably sheets having a laminated structure including a barrier layer and a substrate. The second sheet, which is a non-moisture-proof sheet, may be a sheet consisting of only a substrate, or may be a sheet having a laminated structure including a release layer and a substrate.

[0013] The WVTR of the first sheet and the third sheet is preferably 4 (g / m 2 / 24hr) or less. The lower limit of the WVTR of the first sheet and the third sheet is not particularly limited, and a lower value is preferable. The WVTR of the first sheet and the third sheet is ideally 0 (g / m 2 WVTR is a value measured by the method described in the Examples below.

[0014] For example, when the encapsulating sheet of the present invention is used to encapsulate an electronic device, and the first sheet is not peeled off and used as a highly moisture-proof layer in the electronic device, the first sheet in the present invention has a WVTR of 0.01 (g / m 2 It is preferable to use a moisture-proof sheet having a WVTR of less than 0.005 (g / m2 / 24hr). 2 / 24hr) or less, and more preferably 0.001 (g / m 2 / 24hr) or less, and particularly preferably 0.0005 (g / m 2 / 24hr). The lower limit of the WVTR of this sheet is not particularly limited, and a lower value is preferable. This WVTR is ideally 0 (g / m 2 / 24hr) is most preferred.

[0015] The third sheet is peeled off before the resin composition layer is dried. Therefore, from the viewpoint of simultaneously achieving the suppression of water absorption of the resin composition layer during storage and the suppression of the manufacturing cost of the sealing sheet, the third sheet is preferably a sheet having a WVTR of 0.01 (g / m 2 / 24hr) or more 1(g / m 2 It is preferable to use a moisture-proof sheet with a WVTR of 0.05 (g / m2) or less, taking into account the balance between moisture-proofness and cost. 2 / 24hr) or more, and more preferably 0.8 (g / m 2 / 24hr) or less, more preferably 0.6 (g / m 2 / 24hr).

[0016] The WVTR of the second sheet is preferably 15 (g / m 2 / 24hr) or more. There is no particular upper limit, but the WVTR of the second sheet is usually 20,000 (g / m 2 / 24hr) or less, preferably 15,000 (g / m 2 / 24hr).

[0017] If an opaque moisture-proof sheet such as a metal foil-coated sheet is used as both the first sheet and the third sheet, it becomes difficult to inspect the quality of the resin composition layer. Therefore, when an opaque moisture-proof sheet is used as one of the first sheet and the third sheet, it is preferable to use a transparent moisture-proof sheet as the other. The transparency of a transparent moisture-proof sheet is preferably such that the total light transmittance in D65 light is 85% or more, regardless of its thickness. An "opaque moisture-proof sheet" is defined as a "moisture-proof sheet having a total light transmittance in D65 light of 50% or less." The total light transmittance can be measured with a haze meter HZ-V3 (halogen lamp) manufactured by Suga Test Instruments Co., Ltd., using air as a reference and D65 light.

[0018] In the structure of an electronic device in which an organic EL element is sealed using the sealing sheet of the present invention, when an inorganic film is provided directly on a sealing layer formed from a resin composition layer, or when a highly moisture-proof layer is not required and is not provided, the above-mentioned WVTR is 0.01 (g / m) for both the first sheet and the third sheet. 2 / 24hr) or more 1(g / m 2 It is preferable to use a moisture-proof sheet with a moisture-proofing property of 0.1% or less per 24 hours.

[0019] The structure of the substrate may be a single layer structure or a laminate structure. Examples of the substrate include polyolefins such as polyethylene, polypropylene (PP), and polymethylpentene; polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); and plastic films such as polycarbonate (PC), polyimide (PI), cycloolefin polymer (COP), and polyvinyl chloride. Only one type of plastic film may be used, or two or more types may be used. The substrate is preferably a polyethylene terephthalate film, a cycloolefin polymer film, a polyethylene naphthalate film, or a polycarbonate film, and more preferably a polyethylene terephthalate film or a cycloolefin polymer film. The thickness of the substrate is preferably 10 to 100 μm, more preferably 10 to 75 μm, and even more preferably 10 to 50 μm.

[0020] Examples of the barrier layer include inorganic films such as metal foil (e.g., aluminum foil), silica vapor deposition film, silicon nitride film, and silicon oxide film. The barrier layer may be composed of multiple layers of multiple inorganic films (e.g., metal foil and silica vapor deposition film). The barrier layer may be composed of an organic material and an inorganic material, or may be a composite multilayer of an organic layer and an inorganic film. The thickness of the barrier layer is preferably 0.01 to 100 μm, more preferably 0.05 to 50 μm, and even more preferably 0.05 to 30 μm.

[0021] WVTR is 0.01 (g / m 2 / 24hr), especially moisture-proof sheets with a WVTR of 0.005 (g / m 2 / 24hr) or less, for example, inorganic films such as silicon oxide (silica), aluminum oxide, magnesium oxide, silicon nitride, silicon nitride oxide, SiCN, amorphous silicon, etc., can be produced by laminating them in a single layer or multiple layers on the substrate surface by chemical vapor deposition (e.g., chemical vapor deposition by heat, plasma, ultraviolet light, vacuum heat, vacuum plasma or vacuum ultraviolet light), or physical vapor deposition (e.g., vacuum deposition, sputtering, ion plating, laser deposition, molecular beam epitaxy), etc. (see, for example, JP 2016-185705 A, JP 5719106 A, JP 5712509 A, JP 5292358 A, etc.). In order to prevent cracks in the inorganic film, it is preferable to alternately laminate the inorganic film and a transparent flattening layer (e.g., a transparent plastic layer). The moisture-proof sheet produced by such a method is a sheet having transparency.

[0022] In addition to the moisture-proof sheet produced by the above method, for example, a moisture-proof sheet produced by laminating a metal foil such as SUS foil or aluminum foil, or a substrate and a metal foil with an adhesive, etc., can be mentioned. A moisture-proof sheet made of a metal foil or a substrate and a metal foil is usually opaque.

[0023] The moisture-proof sheet can be produced by, for example, depositing an inorganic film containing an inorganic substance such as silicon oxide (silica), aluminum oxide, magnesium oxide, silicon nitride, silicon oxynitride, SiCN, or amorphous silicon on the surface of a substrate as a barrier layer, or by applying a coating liquid made of a metal oxide and an organic resin having barrier properties to the substrate and drying it (see, for example, JP 2013-108103 A and JP 4028353 A). The moisture-proof sheet produced by such a method is a transparent sheet.

[0024] The moisture-proof sheet may be a commercially available product, such as "Kurarista CI" manufactured by Kuraray Co., Ltd., "Techbarrier HX", "Techbarrier LX" and "Techbarrier L" manufactured by Mitsubishi Plastics, Inc., "IB-PET-PXB" manufactured by Dai Nippon Printing Co., Ltd., "GL, GX Series" manufactured by Toppan Printing Co., Ltd., "PET AL1N30" manufactured by Toyo Aluminum Co., Ltd., and "X-BARRIER" manufactured by Mitsubishi Plastics, Inc.

[0025] The first sheet and the third sheet, which are moisture-proof sheets, may each have a layer other than the substrate and the barrier layer. For example, a laminated sheet obtained by further bonding a substrate to a sheet having a laminated structure including a barrier layer and a substrate using an adhesive (for example, a sheet having a laminated structure including a substrate, an adhesive layer, a barrier layer, and a substrate in this order, or a sheet having a laminated structure including a substrate, an adhesive layer, a substrate, and a barrier layer in this order) may be used as the first sheet and / or the third sheet. Examples of the substrate include those mentioned above. In the present invention, there is no particular limitation on the adhesive, and a commercially available adhesive can be used.

[0026] The first sheet may be a sheet without a release layer. The first sheet may also be a sheet with a release layer, and the release layer may be in contact with the resin composition layer. Examples of the first sheet that is a sheet with a release layer include a sheet having a laminated structure including a barrier layer, a substrate, and a release layer in this order, a sheet having a laminated structure including a substrate, a barrier layer, and a release layer in this order, and a sheet having a laminated structure including a barrier layer, a substrate, an adhesive layer, a substrate, and a release layer in this order. Examples of the substrate and the barrier layer include those described above. In the present invention, there is no particular limitation on the adhesive, and a commercially available adhesive can be used.

[0027] In a preferred embodiment of the present invention, the second sheet is a sheet having a release layer, and the release layer is in contact with the resin composition layer.The second sheet having a release layer may be, for example, a sheet having a laminated structure including a release layer and a substrate.The substrate may be, for example, the above-mentioned.

[0028] The release layer can be formed, for example, by applying a release agent to a substrate and drying it. Alternatively, a plastic film having a release layer may be formed by applying a release agent to a plastic film and drying it, and then the plastic film having the release layer and the moisture-proof sheet composed of the substrate and the barrier layer may be bonded together using an adhesive to form a moisture-proof sheet having a release layer. The drying temperature after application of the release agent is, for example, 100 to 150°C, and the drying time is, for example, 5 to 120 minutes.

[0029] Examples of the release agent include silicone-based release agents, alkyd-based release agents, fluorine-based release agents, and olefin-based release agents. The release layer is preferably formed from a silicone-based release agent or an alkyd-based release agent. The thickness of the release layer is preferably 0.05 to 5 μm, more preferably 0.05 to 3 μm, and even more preferably 0.05 to 2 μm.

[0030] The thickness of the first sheet (when the first sheet is a laminate sheet, its entire thickness) is preferably 10 to 100 μm, more preferably 10 to 62.5 μm, and even more preferably 10 to 55 μm. The thickness of the second sheet (when the second sheet is a laminate sheet, its entire thickness) is preferably 5 to 50 μm, more preferably 7.5 to 40 μm, and even more preferably 10 to 40 μm. The thickness of the third sheet (when the third sheet is a laminate sheet, its entire thickness) is preferably 10 to 100 μm, more preferably 10 to 62.5 μm, and even more preferably 10 to 55 μm.

[0031] As described above, one of the features of the present invention is that the third sheet can be peeled off before the resin composition layer is dried. Examples of the configuration for this purpose include the following: (1) A configuration in which the third sheet is a sheet having an adhesive layer, and the adhesive layer is in contact with the second sheet; (2) The second sheet has an adhesive layer, and the adhesive layer is in contact with the third sheet.

[0032] In the above-mentioned configuration (1), the second sheet may have a release layer. The configuration in which the third sheet is a sheet having an adhesive layer, the second sheet is a sheet having a release layer, and the adhesive layer is in contact with the release layer is included in the above-mentioned configuration (1). The release layer is as described above.

[0033] In the above-mentioned configuration (1), the second sheet may have a release layer on both sides. The configuration in which the third sheet is a sheet having an adhesive layer, the second sheet is a sheet having a release layer on both sides, the adhesive layer contacts one side of the release layer, and the other side of the release layer contacts the resin composition layer is included in the above-mentioned configuration (1). The release layer is as described above.

[0034] In the above-mentioned configuration (2), the third sheet may have a release layer. A configuration in which the second sheet is a sheet having an adhesive layer, the third sheet is a sheet having a release layer, and the adhesive layer is in contact with the release layer is included in the above-mentioned configuration (2).

[0035] In the above-mentioned configuration (2), the third sheet may have a release layer on both sides. The configuration in which the second sheet is a sheet having an adhesive layer, the third sheet is a sheet having a release layer on both sides, and the adhesive layer is in contact with one of the release layers is included in the above-mentioned configuration (2). The release layer is as described above.

[0036] In the configuration (2), the adhesive layer remains on the second sheet after the third sheet is peeled off, and there is a possibility that dust may adhere to the adhesive layer when the second sheet dries. From these viewpoints, the configuration (1) is preferred.

[0037] The 90-degree peel strength between the second sheet and the third sheet is preferably 0.1 gf / inch or more, more preferably 0.2 gf / inch or more, even more preferably 0.25 gf / inch or more, and is preferably 250 gf / inch or less, more preferably 200 gf / inch or less, even more preferably 150 gf / inch or less. This 90-degree peel strength is a value measured by the method described in the examples below.

[0038] When the sealing sheet of the present invention has the above-mentioned configuration (1), the "90-degree peel strength between the second sheet and the third sheet" means the "90-degree peel strength between the second sheet and the adhesive layer of the third sheet." In this embodiment, when the second sheet has a release layer and the release layer is in contact with the adhesive layer of the third sheet, the "90-degree peel strength between the second sheet and the third sheet" means the "90-degree peel strength between the release layer and the adhesive layer."

[0039] When the sealing sheet of the present invention has the above-mentioned configuration (2), the "90-degree peel strength between the second sheet and the third sheet" means the "90-degree peel strength between the adhesive layer of the second sheet and the third sheet." In this embodiment, when the third sheet has a release layer and the release layer is in contact with the adhesive layer of the second sheet, the "90-degree peel strength between the second sheet and the third sheet" means the "90-degree peel strength between the release layer and the adhesive layer."

[0040] The 90-degree peel strength between the resin composition layer and the second sheet is preferably greater than the 90-degree peel strength between the second sheet and the third sheet. With this configuration, peeling of the second sheet can be suppressed when the third sheet is peeled off. The 90-degree peel strength between the resin composition layer and the second sheet is preferably 0.2 gf / inch or more, more preferably 0.25 gf / inch or more, and even more preferably 0.30 gf / inch or more, and is preferably 300 gf / inch or less, more preferably 250 gf / inch or less, and even more preferably 200 gf / inch or less.

[0041] When the second sheet has a release layer and the release layer is in contact with the resin composition layer, "the 90 degree peel strength between the resin composition layer and the second sheet" means "the 90 degree peel strength between the release layer and the resin composition layer."

[0042] The thickness of the adhesive layer is preferably 0.5 to 50 μm, more preferably 1 to 40 μm, and further preferably 1 to 30 μm.

[0043] The adhesive layer can be formed using an adhesive. Any known adhesive can be used as the adhesive. Preferred adhesives include, for example, KR-3704, X-40-3270-1, X-40-3323, X-40-3306, KR-100, KR-101-10, KR-130, KR-3700, KR-3701, X-40-3327, X-40-3240, and X-40-3291-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSR1512, TSR1516, YR3340, YR3286, PSA610-SM, XR37-B9024, and XR37-B6. Silicone adhesives such as BUTYL065, BUTYL268, BUTYL365, CHLOROBUTYL1066, BROMOBUTYL2222, BROMOBUTYL2244, BROMOBUTYL2255 (all manufactured by Japan Butyl Co.), butyl rubber adhesives such as RB100, RB402, RB301, RB101-3 (all manufactured by LANXESS AG), Tafthren Olefin elastomers such as X1102, X1104, X1105, and X1107 (all manufactured by Sumitomo Chemical Co., Ltd.), ARONTAC S-1511X, S-1511 Kai, S-3403, S-3452YKF, S-1601, and S-1605 (all manufactured by Toagosei Co., Ltd.), FINETAC CT-5020, CT-5030, SPS-900-LV, SPS-945NT, SPS-1040NT-25, CT-3088, CT-3850, and CT-6030 (all manufactured by DIC Corporation), SK-Dyne 1501BS4, RE-4, and RE-339 (all manufactured by Soken Chemical & Engineering Co., Ltd.), and Clarity Examples of the adhesive include acrylic adhesives such as LA3320, LA2330, LA2250, LA2270, and LA4285 (all manufactured by Kuraray Co., Ltd.). In addition, a resin composition prepared by appropriately adding an alicyclic saturated hydrocarbon resin to various base polymers can also be used to form the adhesive layer.Examples of the base polymer include olefin-based elastomers such as Tafthren X1102, X1104, X1105, and X1107 (all manufactured by Sumitomo Chemical Co., Ltd.), and styrene-based thermoplastic elastomers such as Septon 1020, 2002, 2004, 2005, 2006, 2063, 2104, 4033, 4044, 4055, 4077, and 4099 (all manufactured by Kuraray Co., Ltd.). In addition, a resin composition containing an olefin-based resin described below can also be used to form the adhesive layer. A resin composition not containing semi-calcined hydrotalcite or other inorganic fillers described below may also be used to form the adhesive layer.

[0044] The adhesive layer can be formed, for example, by applying a liquid adhesive to the second or third sheet and drying it. Alternatively, an adhesive varnish obtained by dissolving an adhesive in a solvent may be used to form the adhesive layer.

[0045] In the present invention, the resin composition layer is not particularly limited, and a known resin composition can be used to form the resin composition layer. In order to effectively seal the organic EL element, etc., the resin composition layer preferably contains an olefin resin and / or an epoxy resin.

[0046] The olefin resin may be used alone or in combination with two or more kinds. The olefin resin is not particularly limited as long as it has a skeleton derived from an olefin monomer. The olefin resin is preferably an ethylene resin, a propylene resin, a butene resin, or an isobutylene resin. These olefin resins may be homopolymers or copolymers such as random copolymers and block copolymers. Examples of the copolymers include copolymers of two or more kinds of olefins, and copolymers of olefins and monomers other than olefins such as non-conjugated dienes and styrene. Examples of preferred copolymers include ethylene-non-conjugated diene copolymers, ethylene-propylene copolymers, ethylene-propylene-non-conjugated diene copolymers, ethylene-butene copolymers, propylene-butene copolymers, propylene-butene copolymers, propylene-butene-non-conjugated diene copolymers, styrene-isobutylene copolymers, styrene-isobutylene-styrene copolymers, and the like. Examples of the olefin resins that are preferably used include isobutylene-modified resins, styrene-isobutylene-modified resins, modified propylene-butene resins, and the like.

[0047] From the viewpoint of imparting excellent physical properties such as adhesiveness, the olefin-based resin preferably includes at least one selected from the group consisting of an olefin-based resin having an acid anhydride group (i.e., a carbonyloxycarbonyl group (-CO-O-CO-)) and an olefin-based resin having an epoxy group, and more preferably includes an olefin-based resin having an acid anhydride group and an olefin-based resin having an epoxy group.

[0048] Examples of the acid anhydride group include a group derived from succinic anhydride, a group derived from maleic anhydride, and a group derived from glutaric anhydride. The olefin resin having an acid anhydride group can be obtained by graft-modifying an olefin resin under radical reaction conditions with an unsaturated compound having an acid anhydride group. The unsaturated compound having an acid anhydride group can also be radically copolymerized with an olefin or the like. Similarly, the olefin resin having an epoxy group can be obtained by graft-modifying an olefin resin under radical reaction conditions with an unsaturated compound having an epoxy group such as glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, allyl glycidyl ether, or the like. The unsaturated compound having an epoxy group can also be radically copolymerized with an olefin or the like.

[0049] The concentration of the acid anhydride group in the olefin resin having an acid anhydride group is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The concentration of the acid anhydride group is obtained from the acid value, which is defined as the number of milligrams of potassium hydroxide required to neutralize the acid present in 1 g of resin, according to the description of JIS K 2501. The amount of the olefin resin having an acid anhydride group in the olefin resin is preferably 0 to 70 mass%, more preferably 10 to 50 mass%.

[0050] The epoxy group concentration in the epoxy group-containing olefin resin is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The epoxy group concentration is calculated from the epoxy equivalent obtained based on JIS K 7236-1995. The amount of the epoxy group-containing olefin resin in the olefin resin is preferably 0 to 70 mass%, more preferably 10 to 50 mass%.

[0051] From the viewpoint of imparting excellent physical properties such as moisture resistance, the olefin resin preferably contains both an olefin resin having an acid anhydride group and an olefin resin having an epoxy group. In such an olefin resin, the acid anhydride group and the epoxy group are reacted by heating to form a crosslinked structure, and a sealing layer (resin composition layer) having excellent moisture resistance can be formed. Although the crosslinked structure can be formed after sealing, for example, in the case of an organic EL element or the like, which is sensitive to heat, it is desirable to form the crosslinked structure when manufacturing the sealing sheet. The ratio of the olefin resin having an acid anhydride group and the olefin resin having an epoxy group is not particularly limited as long as an appropriate crosslinked structure can be formed, but the molar ratio of the epoxy group to the acid anhydride group (epoxy group: acid anhydride group) is preferably 100:10 to 100:200, more preferably 100:50 to 100:150, and particularly preferably 100:90 to 100:110.

[0052] The number average molecular weight of the olefin resin is not particularly limited, but from the viewpoint of providing good coatability of the resin composition varnish and good compatibility with other components in the resin composition, it is preferably 1,000,000 or less, more preferably 750,000 or less, even more preferably 500,000 or less, even more preferably 400,000 or less, even more preferably 300,000 or less, particularly preferably 200,000 or less, and most preferably 150,000 or less. On the other hand, from the viewpoint of preventing repelling during application of the resin composition varnish, expressing the moisture-proofing of the formed resin composition layer, and improving the mechanical strength, the number average molecular weight is preferably 1,000 or more, more preferably 3,000 or more, even more preferably 5,000 or more, even more preferably 10,000 or more, even more preferably 30,000 or more, and particularly preferably 50,000 or more. The number average molecular weight in the present invention is measured by gel permeation chromatography (GPC) method (polystyrene equivalent). Specifically, the number average molecular weight by GPC method is measured at a column temperature of 40°C using Shimadzu Corporation's LC-9A / RID-6A as a measuring device, Showa Denko Corporation's Shodex K-800P / K-804L / K-804L as a column, and toluene or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.

[0053] The olefin resin is preferably amorphous from the viewpoint of suppressing the decrease in fluidity due to the thickening of the varnish. Here, the term "amorphous" means that the olefin resin does not have a clear melting point, and for example, when the melting point of the olefin resin is measured by DSC (differential scanning calorimetry), one that does not show a clear peak can be used.

[0054] There is no particular limitation on the amount of the olefin resin. From the viewpoint of good coating properties, when using an olefin resin, the amount is preferably 80% by mass or less per whole resin composition layer (i.e., per whole non-volatile content of the resin composition), more preferably 75% by mass or less, even more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 55% by mass or less, and particularly preferably 50% by mass or less. On the other hand, from the viewpoint of improving moisture resistance and transparency, the amount of the olefin resin is preferably 1% by mass or more per whole resin composition layer (i.e., per whole non-volatile content of the resin composition), more preferably 3% by mass or more, even more preferably 5% by mass or more, even more preferably 7% by mass or more, even more preferably 10% by mass or more, particularly preferably 35% by mass or more, and most preferably 40% by mass or more.

[0055] Next, specific examples of olefin resins will be described. Specific examples of isobutylene resins include BASF's "OPPANOL B100" (viscosity average molecular weight: 1,110,000) and BASF's "B50SF" (viscosity average molecular weight: 400,000).

[0056] Specific examples of butene resins include "HV-1900" (polybutene, number average molecular weight: 2,900) manufactured by ENEOS Corporation (formerly "JXTG Energy") and "HV-300M" (maleic anhydride modified liquid polybutene (modified "HV-300" (number average molecular weight: 1,400)), number average molecular weight: 2,100, number of carboxy groups constituting the acid anhydride group: 3.2 / molecule, acid value: 43.4 mgKOH / g, acid anhydride group concentration: 0.77 mmol / g) manufactured by Toho Chemical Industry Co., Ltd.

[0057] Specific examples of styrene-isobutylene copolymers include Kaneka's "SIBSTAR T102" (styrene-isobutylene-styrene block copolymer, number average molecular weight: 100,000, styrene content: 30% by mass), Seiko PMC's "T-YP757B" (maleic anhydride-modified styrene-isobutylene-styrene block copolymer, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 100,000), Seiko PMC's "T-YP766" (glycidyl methacrylate-modified styrene-isobutylene-styrene block copolymer, epoxy Examples of the epoxy group concentration include "T-YP8920" manufactured by Seiko PMC (maleic anhydride-modified styrene-isobutylene-styrene copolymer, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 35,800), and "T-YP8930" manufactured by Seiko PMC (glycidyl methacrylate-modified styrene-isobutylene-styrene copolymer, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 48,700).

[0058] Specific examples of ethylene-based resins or propylene-based resins include Mitsui Chemicals' "EPT X-3012P" (ethylene-propylene-5-ethylidene-2-norbornene copolymer), Mitsui Chemicals' "EPT1070" (ethylene-propylene-dicyclopentadiene copolymer), and Mitsui Chemicals' "TAFMER A4085" (ethylene-butene copolymer).

[0059] Specific examples of ethylene-methyl methacrylate copolymers include "T-YP429" manufactured by Seiko PMC (20% by mass toluene solution of maleic anhydride-modified ethylene-methyl methacrylate copolymer (amount of methyl methacrylate units per 100% by mass of ethylene units and methyl methacrylate units: 32% by mass, acid anhydride group concentration: 0.46 mmol / g, number average molecular weight: 2,300)) and "T-YP430" manufactured by Seiko PMC (maleic anhydride-modified ethylene-methyl methacrylate copolymer, amount of methyl methacrylate units per 100% by mass of ethylene units and methyl methacrylate units: 32% by mass, acid anhydride group concentration: 0.46 mmol / g, number average molecular weight: 2,300)). % methyl methacrylate unit amount: 32 mass%, acid anhydride group concentration: 1.18 mmol / g, number average molecular weight: 4,500), Seiko PMC's "T-YP431" (glycidyl methacrylate modified ethylene-methyl methacrylate copolymer (epoxy group concentration: 0.64 mmol / g, number average molecular weight: 2,400) 20 mass% toluene solution), and Seiko PMC's "T-YP432" (glycidyl methacrylate modified ethylene-methyl methacrylate copolymer, epoxy group concentration: 1.63 mmol / g, number average molecular weight: 3,100).

[0060] Specific examples of propylene-butene copolymers include "T-YP341" manufactured by Seiko PMC (a 20% by mass Swazol solution of glycidyl methacrylate-modified propylene-butene random copolymer (amount of butene units per 100% by mass of propylene units and butene units: 29% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 155,000)), "T-YP279" manufactured by Seiko PMC (maleic anhydride-modified propylene-butene random copolymer, amount of butene units per 100% by mass of propylene units and butene units: 36% by mass, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 35,000), and "T-YP276" manufactured by Seiko PMC (glycidyl methacrylate-modified propylene-butene random copolymer, amount of propylene units and butene units: 36% by mass, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 35,000). butene unit amount per 100% by mass of units: 36% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 57,000), Seiko PMC's "T-YP312" (40% by mass toluene solution of maleic anhydride modified propylene-butene random copolymer (amount of butene units per 100% by mass of propylene units and butene units: 29% by mass, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 60,900)), and Seiko PMC's "T-YP313" (20% by mass toluene solution of glycidyl methacrylate modified propylene-butene random copolymer (amount of butene units per 100% by mass of propylene units and butene units: 29% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 155,000)).

[0061] When the olefin resin contains an olefin resin having an epoxy group, an olefin resin having a functional group other than an acid anhydride group that can react with the epoxy group may be used. Examples of the functional group include a hydroxyl group, a phenolic hydroxyl group, an amino group, and a carboxyl group.

[0062] When the olefin resin contains an olefin resin having an acid anhydride group, an olefin resin having a functional group other than an epoxy group that can react with the acid anhydride group may be used. Examples of the functional group include a hydroxyl group, a primary or secondary amino group, a thiol group, and an oxetane group.

[0063] There are no limitations on the epoxy resin that can be used so long as it has, on average, two or more epoxy groups per molecule. Examples of epoxy resins include bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, biphenyl type epoxy resins, biphenyl aralkyl type epoxy resins, naphthol type epoxy resins, naphthalene type epoxy resins, bisphenol F type epoxy resins, phosphorus-containing epoxy resins, bisphenol S type epoxy resins, aromatic glycidylamine type epoxy resins (e.g., tetraglycidyldiaminodiphenylmethane, triglycidyl-p-aminophenol, diglycidyl toluidine, diglycidyl aniline, etc.), alicyclic epoxy resins, aliphatic chain epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, epoxy resins having a butadiene structure, diglycidyl ethers of bisphenols, diglycidyl ethers of naphthalene diols, diglycidyl ethers of phenols, and diglycidyl ethers of alcohols, as well as alkyl substituted, halogenated and hydrogenated versions of these epoxy resins. The epoxy resin may be used alone or in combination of two or more kinds.

[0064] From the viewpoint of reactivity and the like, the epoxy equivalent of the epoxy resin is preferably 50 to 5,000, more preferably 50 to 3,000, more preferably 80 to 2,000, more preferably 100 to 1,000, more preferably 120 to 1,000, more preferably 140 to 300. The "epoxy equivalent" refers to the number of grams (g / eq) of a resin containing 1 gram equivalent of epoxy groups, and is measured according to the method specified in JIS K 7236. The weight average molecular weight of the epoxy resin is preferably 5,000 or less.

[0065] The epoxy resin may be either liquid or solid, and both liquid and solid epoxy resins may be used. Here, "liquid" and "solid" refer to the state of the epoxy resin at room temperature (25°C) and normal pressure (1 atm).

[0066] The amount of the epoxy resin is not particularly limited. When the epoxy resin is used, the amount of the epoxy resin is preferably 20 to 80 mass % based on the total amount of the resin composition layer (i.e., based on the total amount of non-volatile content of the resin composition), more preferably 30 to 70 mass %, and further preferably 50 to 65 mass %.

[0067] From the viewpoint of the moisture blocking property of the sealing sheet of the present invention, the resin composition layer preferably contains semi-calcined hydrotalcite. Only one type of semi-calcined hydrotalcite may be used, or two or more types of semi-calcined hydrotalcite may be used.

[0068] Hydrotalcite can be classified into uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite.

[0069] Uncalcined hydrotalcite is, for example, natural hydrotalcite (Mg6Al2(OH) 16 It is a metal hydroxide with a layered crystal structure, such as the metal hydroxide [Mg 1-X Al X (OH)2] X+ and the intermediate layer [(CO3) X / 2 mH2O] X- The uncalcined hydrotalcite in the present invention is a concept including hydrotalcite-like compounds such as synthetic hydrotalcite. Examples of the hydrotalcite-like compounds include those represented by the following formula (I) and the following formula (II).

[0070] [M 2+ 1-x M 3+ x (OH)2] x+ ·[(A n- )x / n ·mH2O] x- (I) (wherein M 2+ represents a divalent metal ion such as Mg 2+ , Zn 2+ ; M 3+ represents a trivalent metal ion such as Al 3+ , Fe 3+ ; A n- represents an n-valent anion such as CO3 2- , Cl - , NO3 - ; 0 < x < 1, 0 ≦ m < 1, and n is a positive number.) In formula (I), M 2+ is preferably Mg 2+ ; M 3+ is preferably Al 3+ ; and A n- is preferably CO3 2- .

[0071] M 2+ x Al2(OH) 2x+6-nz (A n- ) z ·mH2O (II) (wherein M 2+ represents a divalent metal ion such as Mg 2+ , Zn 2+ ; A n- represents an n-valent anion such as CO3 2- , Cl - , NO 3- ; x is a positive number of 2 or more, z is a positive number of 2 or less, m is a positive number, and n is a positive number.) In formula (II), M 2+ is preferably Mg 2+ ; and A n- is preferably CO3 2- .

[0072] Semi-calcined hydrotalcite is a metal hydroxide obtained by calcining uncalcined hydrotalcite and having a layered crystal structure in which the amount of interlayer water is reduced or eliminated. When explained using a composition formula, "interlayer water" refers to "H2O" described in the composition formula of the above-mentioned uncalcined natural hydrotalcite and hydrotalcite-like compounds.

[0073] On the other hand, calcined hydrotalcite is obtained by calcining uncalcined hydrotalcite or semi-calcined hydrotalcite, and refers to a metal oxide having an amorphous structure in which not only interlayer water but also hydroxyl groups have disappeared through condensation dehydration.

[0074] Uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite can be distinguished by their saturated water absorption. The saturated water absorption of semi-calcined hydrotalcite is 1% by mass or more and less than 20% by mass. On the other hand, the saturated water absorption of uncalcined hydrotalcite is less than 1% by mass, and the saturated water absorption of calcined hydrotalcite is 20% by mass or more.

[0075] The term "saturated water absorption" in the present invention refers to the rate of mass increase relative to the initial mass when 1.5 g of uncalcined hydrotalcite, semi-calcined hydrotalcite or calcined hydrotalcite is weighed out on a balance, the initial mass is measured, and the sample is allowed to stand for 200 hours in a small environmental tester (SH-222 manufactured by Espec Corp.) set at atmospheric pressure, 60°C and 90% RH (relative humidity), and is calculated using the following formula (i): Saturated water absorption rate (mass%) = 100 × (mass after moisture absorption – initial mass) / initial mass (i) It can be found by:

[0076] The saturated water absorption of the semi-calcined hydrotalcite is preferably 3% by mass or more and less than 20% by mass, and more preferably 5% by mass or more and less than 20% by mass.

[0077] Furthermore, uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite can be distinguished by the rate of weight loss on heat measured by thermogravimetric analysis. The rate of weight loss on heat of semi-calcined hydrotalcite at 280°C is less than 15% by mass, and the rate of weight loss on heat of semi-calcined hydrotalcite at 380°C is 12% by mass or more. On the other hand, the rate of weight loss on heat of uncalcined hydrotalcite at 280°C is 15% by mass or more, and the rate of weight loss on heat of calcined hydrotalcite at 380°C is less than 12% by mass.

[0078] Thermogravimetric analysis can be performed using a Hitachi High-Tech Science TG / DTA EXSTAR6300 by weighing 5 mg of hydrotalcite into an aluminum sample pan, leaving the pan open and uncovered, under conditions of a nitrogen flow rate of 200 mL / min and a heating rate of 10°C / min from 30°C to 550°C. The thermal weight loss rate is calculated using the following formula (ii): Thermogravimetric reduction rate (mass%) = 100 × (mass before heating – mass when the specified temperature is reached) / mass before heating (ii) It can be found by:

[0079] In addition, uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite can be distinguished by the peaks and relative intensity ratios measured by powder X-ray diffraction. Semi-calcined hydrotalcite shows a peak split into two at 2θ of around 8 to 18° by powder X-ray diffraction, or a peak having a shoulder due to the synthesis of two peaks, and the relative intensity ratio (low-angle diffraction intensity / high-angle diffraction intensity) of the diffraction intensity of the peak or shoulder appearing on the low-angle side (= low-angle diffraction intensity) and the diffraction intensity of the peak or shoulder appearing on the high-angle side (= high-angle diffraction intensity) is 0.001 to 1,000. On the other hand, uncalcined hydrotalcite has only one peak near 8 to 18°, or the relative intensity ratio of the diffraction intensity of the peak or shoulder appearing on the low-angle side and the peak or shoulder appearing on the high-angle side is outside the above-mentioned range. Calcined hydrotalcite does not have a characteristic peak in the 8° to 18° region, but has a characteristic peak at 43°. Powder X-ray diffraction measurements were performed using a powder X-ray diffractometer (PANalytical, Empyrean) under the following conditions: anticathode CuKα (1.5405 Å), voltage: 45 V, current: 40 mA, sampling width: 0.0260°, scanning speed: 0.0657° / s, measurement diffraction angle range (2θ): 5.0131 to 79.9711°. Peak search was performed using the peak search function of the software attached to the diffractometer under the conditions of "minimum significance: 0.50, minimum peak tip: 0.01°, maximum peak tip: 1.00°, peak base width: 2.00°, method: minimum value of second derivative".

[0080] The BET specific surface area of ​​semi-calcined hydrotalcite is 1 to 250 m 2 / g is preferable, and 5 to 200m 2 The BET specific surface area of ​​the semi-calcined hydrotalcite can be calculated by the BET multipoint method using a specific surface area measuring device (Macsorb HM Model 1210, manufactured by Mountech Co., Ltd.) in accordance with the BET method, after adsorbing nitrogen gas onto the surface of the sample.

[0081] The particle size of the semi-calcined hydrotalcite is preferably 1 to 1,000 nm, and more preferably 10 to 800 nm. The particle size of the semi-calcined hydrotalcite is the median size of a particle size distribution determined on a volume basis by a laser diffraction / scattering particle size distribution measurement (JIS Z 8825).

[0082] The semi-calcined hydrotalcite may be surface-treated with a surface treatment agent. Examples of the surface treatment agent that may be used for the surface treatment include higher fatty acids, alkyl silanes, and silane coupling agents, and among these, higher fatty acids and alkyl silanes are preferred. One or more types of surface treatment agents may be used.

[0083] Examples of higher fatty acids include higher fatty acids having 14 or more carbon atoms, such as stearic acid, montanic acid, myristic acid, palmitic acid, etc., and among these, stearic acid is preferred. These may be used alone or in combination of two or more.

[0084] Examples of alkylsilanes include methyltrimethoxysilane, ethyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, octadecyltrimethoxysilane, dimethyldimethoxysilane, octyltriethoxysilane, n-octadecyldimethyl(3-(trimethoxysilyl)propyl)ammonium chloride, etc. These may be used alone or in combination.

[0085] Examples of the silane coupling agent include epoxy-based silane coupling agents such as 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyl(dimethoxy)methylsilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 11-mercaptoundecyltrimethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, N-phenyl-3-aminopropyltrimethoxysilane, N-methylaminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane. Examples of the silane coupling agents include amino-based silane coupling agents such as aminopropyldimethoxymethylsilane; ureido-based silane coupling agents such as 3-ureidopropyltriethoxysilane; vinyl-based silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, and vinylmethyldiethoxysilane; styryl-based silane coupling agents such as p-styryltrimethoxysilane; acrylate-based silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane; isocyanate-based silane coupling agents such as 3-isocyanatepropyltrimethoxysilane; sulfide-based silane coupling agents such as bis(triethoxysilylpropyl)disulfide and bis(triethoxysilylpropyl)tetrasulfide; phenyltrimethoxysilane, methacryloxypropyltrimethoxysilane, imidazole silane, and triazine silane. These can be used alone or in combination.

[0086] The surface treatment of the semi-calcined hydrotalcite can be carried out, for example, by adding and spraying the surface treatment agent while stirring and dispersing the untreated semi-calcined hydrotalcite at room temperature in a mixer, and stirring for 5 to 60 minutes. As the mixer, a known mixer can be used, for example, a V blender, a ribbon blender, a bubble cone blender, or the like, a mixer such as a Henschel mixer or a concrete mixer, a ball mill, a cutter mill, or the like. In addition, when the semi-calcined hydrotalcite is pulverized in a ball mill, the above-mentioned higher fatty acid, alkylsilanes, or silane coupling agents can be added to perform the surface treatment. The amount of the surface treatment agent used varies depending on the type of semi-calcined hydrotalcite or the type of surface treatment agent, etc., but is preferably 1 to 10 parts by mass per 100 parts by mass of semi-calcined hydrotalcite that has not been surface-treated. In the present invention, the surface-treated semi-calcined hydrotalcite is also included in the "semi-calcined hydrotalcite".

[0087] The amount of semi-calcined hydrotalcite is not particularly limited. In terms of the moisture blocking property of the sealing sheet, when semi-calcined hydrotalcite is used, the amount thereof is preferably 3 to 50 mass% based on the entire resin composition layer (i.e., based on the entire non-volatile content of the resin composition), more preferably 5 to 45 mass%, and further preferably 10 to 40 mass%.

[0088] Examples of semi-calcined hydrotalcites include "DHT-4C" (Kyowa Chemical Industry Co., Ltd., particle size: 400 nm) and "DHT-4A-2" (Kyowa Chemical Industry Co., Ltd., particle size: 400 nm). Examples of calcined hydrotalcites include "KW-2200" (Kyowa Chemical Industry Co., Ltd., particle size: 400 nm), and examples of uncalcined hydrotalcites include "DHT-4A" (Kyowa Chemical Industry Co., Ltd., particle size: 400 nm), "STABIACE HT-1, HT-7, HT-P" (Sakai Chemical Industry Co., Ltd.).

[0089] The resin composition layer may contain other components different from the above-mentioned olefin resin, epoxy resin, and semi-calcined hydrotalcite. There is no limitation on the other components, and those known as components of sealing resin compositions can be used. Examples of the other components include curing agents, curing accelerators, other resins different from the olefin resin and the epoxy resin, other inorganic fillers different from the semi-calcined hydrotalcite, silane coupling agents, etc. These other components may be used alone or in combination of two or more.

[0090] When an olefin resin having an epoxy group and / or an epoxy resin is used, it is preferable to use a curing agent or a combination of a curing agent and a curing accelerator for curing the resin.

[0091] In the present invention, the resin composition layer may contain other resins different from the olefin resin and the epoxy resin. Examples of other resins include tackifier resins and thermoplastic resins different from the olefin resin (e.g., phenoxy resins, etc.). The phenoxy resins may have epoxy groups, similar to epoxy resins. The epoxy equivalent of the phenoxy resin is preferably more than 5,000 and not more than 16,000, more preferably 10,000 or more and not more than 16,000.

[0092] In the present invention, the resin composition layer may contain other inorganic fillers different from the semi-calcined hydrotalcite. Examples of other inorganic fillers include uncalcined hydrotalcite, calcined hydrotalcite, talc, silica, alumina, barium sulfate, clay, mica, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, boron nitride, aluminum borate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, and calcium zirconate. The amount of other inorganic fillers is preferably 0 to 12% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 8% by mass based on the total amount of the resin composition layer (i.e., based on the total amount of non-volatile content of the resin composition).

[0093] The thickness of the resin composition layer is preferably from 5 to 75 μm, more preferably from 5 to 50 μm, and further preferably from 5 to 30 μm.

[0094] The sealing sheet of the present invention can be produced, for example, by applying a resin composition varnish to a first sheet and drying it to form a resin composition layer, and then laminating a second sheet and a third sheet in that order on the obtained resin composition layer.

[0095] The resin composition varnish is prepared by mixing the components of the resin composition and an organic solvent using a kneading roller, a rotary mixer, etc. The non-volatile content of the resin composition varnish is preferably 20 to 80% by mass, more preferably 30 to 70% by mass.

[0096] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetate esters such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and the like; and aromatic mixed solvents such as solvent naphtha. Examples of commercial aromatic mixed solvents include "Swasol" (manufactured by Maruzen Oil Co., Ltd.) and "Ipsol" (manufactured by Idemitsu Kosan Co., Ltd.). Only one type of organic solvent may be used, or two or more types may be used.

[0097] The drying conditions for forming the resin composition layer are not particularly limited, but the drying temperature is, for example, 80 to 130° C., and the drying time is, for example, 3 to 60 minutes. When the resin composition layer contains an epoxy resin, the drying temperature is preferably 80 to 100° C., and the drying time is preferably 5 to 90 minutes. When the resin composition layer does not contain an epoxy resin but contains an olefin resin, the drying temperature is preferably 80 to 130° C., and the drying time is preferably 15 to 60 minutes.

[0098] After forming a resin composition layer on the first sheet, the second sheet and the third sheet are sequentially laminated on the obtained resin composition layer to produce the sealing sheet of the present invention. For lamination, known equipment such as a roll laminator, a press machine, a vacuum pressure laminator, etc. can be used.

[0099] The encapsulating sheet of the present invention is useful as a sheet used for encapsulating an electronic device that is sensitive to moisture. The electronic device is preferably an organic EL device, a quantum dot device, or a solar cell. EXAMPLES

[0100] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is of course possible to carry out the present invention with appropriate modifications within the scope of the above and below spirit, and all of these modifications are included in the technical scope of the present invention.

[0101] <Sheet> The water vapor transmission rate (WVTR) and other properties of each sheet (each moisture-proof sheet and each polyethylene terephthalate (PET) film with a release layer) used in the following examples and comparative examples, measured by the method described below, are shown in Table 1 below.

[0102] [Table 1]

[0103] Sheet A (PET with barrier layer) listed in Table 1 is a moisture-proof sheet having a barrier layer (silica vapor deposition film) on one side of the PET film, with a laminated structure of barrier layer / PET film; Sheet B (PET1 with silicone release layer) and Sheet C (PET2 with silicone release layer) are both sheets having a laminated structure of silicone release layer / PET film, with a silicone release layer on one side of the PET film; and Sheet E (PET3 with silicone release layer) is a sheet having a laminated structure of silicone release layer / PET film / silicone release layer, with silicone release layers on both sides of the PET film.

[0104] As the first sheet in Examples 1 and 2 and Comparative Examples 1 and 2, the following moisture-proof sheets were used. Sheet F: A moisture-proof sheet having a laminated structure of PET film / barrier layer / adhesive layer / PET film / silicone release layer obtained by bonding the surface opposite to the release layer of Sheet B (PET1 with silicone release layer) and the surface of the barrier layer of Sheet A with an adhesive (thickness of the entire moisture-proof sheet: 50 μm, water vapor transmission rate (WVTR) of the entire moisture-proof sheet: 0.06 (g / m 2 / 24hr)

[0105] As the second sheet in Comparative Example 1, the following moisture-proof sheet was used. Sheet G: A moisture-proof sheet having a laminated structure of PET film / barrier layer / adhesive layer / PET film / silicone release layer obtained by bonding the surface opposite the release layer of Sheet C (PET2 with silicone release layer) to the surface of the barrier layer of Sheet A with an adhesive (thickness of the entire moisture-proof sheet: 37 μm, water vapor transmission rate (WVTR) of the entire moisture-proof sheet: 0.12 ((g / m 2 / 24hr)

[0106] To produce the third sheets in Examples 1 and 2, the following moisture-proof sheets were used. Sheet H: A moisture-proof sheet having a laminated structure of PET film / barrier layer / adhesive layer / PET film obtained by bonding the barrier layer surface of Sheet D (PET film) and Sheet A with an adhesive (thickness of the entire moisture-proof sheet: 37 μm, water vapor transmission rate (WVTR) of the entire moisture-proof sheet: 0.12 ((g / m 2 / 24hr)

[0107] In Examples 1 and 2 and Comparative Examples 1 and 2, encapsulating sheets were prepared on the premise that the second sheet was peeled off when the encapsulating layer of the electronic device was formed. In Examples 1 and 2, encapsulating sheets were prepared on the premise that the third sheet was peeled off before the resin composition layer was dried.

[0108] As the third sheet in the encapsulating sheets of Examples 1 and 2, the following moisture-proof sheets were used, respectively. Sheet H with adhesive layer A: A moisture-proof sheet with a laminated structure of silicone adhesive layer / PET film / barrier layer / adhesive layer / PET film, in which a silicone adhesive layer (5 μm) is provided on the opposite side of the PET film laminated with the barrier layer of Sheet H (total thickness of moisture-proof sheet: 42 μm) Sheet H with adhesive layer B: A moisture-proof sheet with a laminated structure of butyl rubber adhesive layer / PET film / barrier layer / adhesive layer / PET film, in which a butyl rubber adhesive layer (5 μm) is provided on the opposite side of the PET film laminated with the barrier layer of Sheet H (total thickness of moisture-proof sheet: 42 μm)

[0109] The sheet H with adhesive layer A was manufactured as follows. First, 100 parts by mass of silicone resin ("KR-3704" manufactured by Shin-Etsu Chemical Co., Ltd.) was dissolved in 50 parts by mass of toluene, and then 0.5 parts by mass of crosslinker ("CAT-PL-50T" manufactured by Shin-Etsu Chemical Co., Ltd.) was added to the obtained solution, and the obtained mixture was uniformly stirred with a high-speed rotating mixer to obtain a varnish. The varnish was uniformly applied to the sheet H with a die coater, and heated at 130°C for 1 minute to obtain a sheet H with a weak adhesive layer A (total thickness of moisture-proof sheet: 42 μm).

[0110] The sheet H with adhesive layer B was manufactured as follows. First, a mixture of 15 parts by mass of butyl rubber ("IIR065" manufactured by Japan Butyl Co., Ltd.) and 85 parts by mass of toluene was uniformly stirred in a high-speed rotating mixer to obtain a varnish. The varnish was uniformly applied to the sheet H with a die coater, and heated at 130°C for 3 minutes to obtain a sheet H with a weak adhesive layer B (total thickness of moisture-proof sheet: 42 μm).

[0111] <Production of Resin Composition Varnish> Production Example 1: Production of olefin-based resin composition varnish A 60% by mass Swazol solution of cyclohexane ring-containing saturated hydrocarbon resin ("Alcon P125" manufactured by Arakawa Chemical Industries, Ltd.) was mixed with 130 parts by mass of a maleic anhydride-modified liquid polyisobutylene ("HV-300M" manufactured by Toho Chemical Industry Co., Ltd.), 35 parts by mass of polybutene ("HV-1900" manufactured by JXTG Nippon Oil & Energy Corporation), and commercially available semi-calcined hydrotalcite (BET specific surface area: 15 m 2 A mixture was obtained by dispersing 100 parts by mass of glycidyl methacrylate modified polypropylene-polybutene copolymer (200 parts by mass of Swazol solution (T-YP341 manufactured by Seiko PMC Corporation) of 20% by mass, a curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol) of 0.5 parts by mass, and 16 parts by mass of toluene, and the mixture was uniformly dispersed in a high-speed rotating mixer to obtain an olefin resin composition varnish.

[0112] <Water absorption rate of hydrotalcite> The hydrotalcite used in the examples and comparative examples was weighed out in an amount of 1.5 g on a balance, and the initial mass was measured. The hydrotalcite was left to stand for 200 hours in a small environmental tester (SH-222 manufactured by ESPEC Corp.) set at atmospheric pressure, 60°C, and 90% RH (relative humidity), and the mass after moisture absorption was measured, and the saturated water absorption rate was calculated using the above formula (i). The results are shown in Table 2.

[0113] <Thermal weight loss rate of hydrotalcite> Thermogravimetric analysis of the hydrotalcite used in the examples and comparative examples was carried out using a Hitachi High-Tech Science TG / DTA EXSTAR6300. 10 mg of hydrotalcite was weighed into an aluminum sample pan, and the pan was heated from 30°C to 550°C at a rate of 10°C / min in an open, uncovered state in a nitrogen atmosphere with a flow rate of 200 mL / min. The thermal weight loss rates at 280°C and 380°C were calculated using the above formula (ii). The results are shown in Table 2.

[0114] <Powder X-ray diffraction> Powder X-ray diffraction measurements were performed using a powder X-ray diffractometer (PANalytical, Empyrean) under the following conditions: anticathode CuKα (1.5405 Å), voltage: 45 V, current: 40 mA, sampling width: 0.0260°, scanning speed: 0.0657° / s, measurement diffraction angle range (2θ): 5.0131 to 79.9711°. Peak search was performed using the peak search function of the software attached to the diffractometer under the conditions of "minimum significance: 0.50, minimum peak tip: 0.01°, maximum peak tip: 1.00°, peak base width: 2.00°, method: minimum value of second derivative." Two split peaks that appeared within the 2θ range of 8 to 18 degrees, or a peak with a shoulder formed by combining two peaks, were detected, and the diffraction intensity of the peak or shoulder that appeared on the low angle side (= low angle side diffraction intensity) and the diffraction intensity of the peak or shoulder that appeared on the high angle side (= high angle side diffraction intensity) were measured, and the relative intensity ratio (= low angle side diffraction intensity / high angle side diffraction intensity) was calculated. The results are shown in Table 2.

[0115] [Table 2]

[0116] From the results of saturated water absorption, thermal weight loss and powder X-ray diffraction, it was confirmed that the hydrotalcite used in the examples and comparative examples was "semi-calcined hydrotalcite".

[0117] <Production of Encapsulating Sheet> Example 1 Sheet F was used as the first sheet, Sheet C was used as the second sheet, and "Sheet H with adhesive layer A" was used as the third sheet.

[0118] The olefin-based resin composition varnish obtained in Production Example 1 was uniformly applied to the silicone release layer of the first sheet (Sheet F) using a die coater and heated at 130°C for 60 minutes to obtain a laminated product 1 (resin composition layer thickness: 20 μm) having a laminated structure of the first sheet (=PET film / barrier layer / adhesive layer / PET film / silicone release layer) / resin composition layer.

[0119] Next, the adhesive layer of the third sheet (sheet H with adhesive layer A) was bonded to the PET film of the second sheet (sheet C) to prepare laminate 2 having a laminated structure of the second sheet (= silicone release layer / PET film) / third sheet (= silicone-based adhesive layer / PET film / barrier layer / adhesive layer / PET film).

[0120] The silicone release layer of the obtained laminate 2 was attached to the resin composition layer of the obtained laminate 1 so that the silicone release layer was in contact with the resin composition layer of the obtained laminate 1, to produce a sealing sheet having a laminated structure of the first sheet (=barrier layer / PET film / adhesive layer / PET film / silicone release layer) / resin composition layer / second sheet (=silicone release layer / PET film) / third sheet (=silicone adhesive layer / PET film / barrier layer / adhesive layer / PET film), and wound into a roll. The roll-shaped sealing sheet was slit to a width of 507 mm to obtain a sealing sheet having a size of 507 x 336 mm.

[0121] The 90 degree peel strength between the second sheet and the third sheet (more specifically, the 90 degree peel strength between the second sheet (sheet C) and the adhesive layer A of the third sheet (sheet H with adhesive layer A)) was measured by the method described below and was found to be 75 gf / inch.

[0122] The 90 degree peel strength between the resin composition layer and the second sheet (more specifically, the 90 degree peel strength between the resin composition layer and the silicone release layer of the second sheet (Sheet C)) was measured by the method described below and was found to be 80 gf / inch.

[0123] Example 2 An encapsulating sheet was produced in the same manner as in Example 1, except that "sheet H with adhesive layer B" was used as the third sheet, and sheet E was used as the second sheet.

[0124] The 90 degree peel strength between the second sheet and the third sheet (more specifically, the 90 degree peel strength between the silicone release layer of the second sheet (sheet E) and the adhesive layer B of the third sheet (sheet H with adhesive layer B)) was measured by the method described below and was found to be 30 gf / inch.

[0125] The 90 degree peel strength between the resin composition layer and the second sheet (more specifically, the 90 degree peel strength between the resin composition layer and the silicone release layer of the second sheet (Sheet E)) was measured by the method described below and was found to be 75 gf / inch.

[0126] Comparative Example 1 Sheet F was used as the first sheet and Sheet G was used as the second sheet.

[0127] The olefin-based resin composition varnish obtained in Production Example 1 was uniformly applied to the silicone release layer of the first sheet (Sheet F) using a die coater and heated at 130°C for 60 minutes to obtain a laminated product 1 (resin composition layer thickness: 20 μm) having a laminated structure of the first sheet (=PET film / barrier layer / adhesive layer / PET film / silicone release layer) / resin composition layer.

[0128] The second sheet (sheet G) was laminated so that the silicone release layer of the obtained laminate 1 was in contact with the resin composition layer, to produce a sealing sheet having a laminated structure of the first sheet (=PET film / barrier layer / adhesive layer / PET film / silicone release layer) / resin composition layer / second sheet (=silicone release layer / PET film / adhesive layer / barrier layer / PET film), and wound into a roll. The roll-shaped sealing sheet was slit to a width of 507 mm to obtain a sealing sheet having a size of 507×336 mm.

[0129] Comparative Example 2 An encapsulating sheet was produced in the same manner as in Comparative Example 1, except that Sheet C was used as the second sheet.

[0130] The first to third sheets used in Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Table 3 below.

[0131] [Table 3]

[0132] <Measurement method> (1) Measurement of water vapor transmission rate (WVTR) The water vapor permeability of the sheet was determined by an infrared sensor method in accordance with JIS K7129B. Specifically, the water vapor permeability of the sheet (g / m 2 / 24hr) was measured in an atmosphere of temperature 40°C and relative humidity 90% using a water vapor transmission rate measuring device (MOCON, PERMATRAN-W 3 / 34).

[0133] (2) Measurement of 90 degree peel strength The 90 degree peel strength between the second sheet and the third sheet in Examples 1 and 2 was measured as follows. First, the sealing sheet prepared in Examples 1 and 2 was cut to a length of 25 mm x 140 mm, and the first sheet was attached to a glass epoxy board cut to a length of 25 mm x 100 mm and fixed with double-sided tape. The prepared sample was set in a tensile tester VPA-H100 manufactured by Kyowa Interface Science Co., Ltd., and the peel strength between the second sheet and the third sheet was measured under the conditions of 90 degrees and a speed of 300 mm / sec. Moreover, the 90 degree peel strength between the resin composition layer and the second sheet in Examples 1 and 2 was measured in the same manner.

[0134] (3) Measurement of moisture content The water contents of the resin composition layers of the encapsulating sheets produced in Examples 1 and 2 and Comparative Examples 1 and 2 before and after standing and after drying were measured as follows.

[0135] (3-1) Moisture content A before storage The sealing sheet produced within 8 hours was cut into 7 cm squares, and the resin composition layer taken out from the cut was used as a sample before standing, and the moisture content was measured using a Karl Fischer moisture meter ("Trace Moisture Meter CA-310" manufactured by Mitsubishi Chemical Analytech Co., Ltd.) using a coulometric titration method. The moisture content A before standing is shown in Table 4 below.

[0136] The apparatus is composed of a glass container in which a heatable sample is placed, and a titration device containing a reaction solution for titrating the water vaporized when the sample is heated. The vaporized water moves from the glass container to the reaction solution side of the titration device by flowing nitrogen at a flow rate of 250±25 ml / min. The measurement was carried out by placing the sample in a glass container substituted with a nitrogen atmosphere (water vapor amount <0.1 ppm (by mass)), titrating the amount of vaporized water under conditions of 250°C, and calculating the water content of the resin composition layer. Note that the unit of water content "ppm" described below is based on mass.

[0137] (3-2) Moisture content after standing B The sealing sheet cut into 7 cm squares was left for 24 hours under an atmosphere of 25°C temperature and 50% RH humidity, and the resin composition layer taken out from the sealing sheet was used as a sample after leaving, and its moisture content was measured in the same manner as above. The moisture content B after leaving is shown in Table 4 below.

[0138] The ratio of the moisture content B after standing measured as described above to the moisture content A before standing (i.e., moisture content B after standing / moisture content A before standing, hereinafter sometimes referred to as "B / A") was calculated. This ratio is also shown in Table 4 below.

[0139] From B / A, the encapsulating sheet was evaluated according to the following Criteria 1. The results are also shown in Table 4 below. (Criterion 1) Good: B / A is less than 2.0 × (bad): B / A is 2.0 or more

[0140] (3-3) Moisture content after drying C The encapsulating sheet was cut into a 7 cm square and left for 24 hours under an atmosphere of 25°C and 50% RH humidity, and then heated to 150°C for 30 minutes to dry. The encapsulating sheets of Examples 1 and 2 were dried after peeling off the third sheet. The encapsulating sheets of Examples 1 and 2 and Comparative Examples 1 and 2 were all dried without peeling off the second sheet. After drying, the resin composition layer taken out from the encapsulating sheet was used as a sample after drying, and its moisture content was measured in the same manner as above. The moisture content C after drying is shown in Table 4 below.

[0141] The ratio of the moisture content C after drying measured as described above to the moisture content A before standing (i.e., moisture content C after drying / moisture content A before standing, hereinafter sometimes referred to as "C / A") was calculated. This ratio is also shown in Table 4 below.

[0142] Based on the moisture content C and C / A after drying, the encapsulating sheet was evaluated according to the following criteria 2. The results are also shown in the table below. (Criterion 2) ○ (Good): C / A is less than 0.5 △(Acceptable): C / A is 0.5 or more and less than 0.8 × (bad): C / A is 0.8 or more

[0143] (4) Measurement of Ca surface deterioration behavior In a simulation experiment using a glass substrate on which a Ca film was formed instead of an organic EL element, the sealing performance of the sealing sheet dried in the same manner as in the method described in "(2-3) Moisture content after drying C" was evaluated.

[0144] Specifically, Ca was first evaporated onto a glass substrate (thickness: 700 μm, width: 50 mm, length: 50 mm) to form a Ca film (thickness: about 300 nm, width: 40 mm, length: 40 mm). The resulting glass substrate had a sealing width of 2 mm around the Ca film (i.e., the width where the glass substrate without the Ca film contacts the sealing sheet).

[0145] Next, after drying the sealing sheet, the first sheet was peeled off, and the sealing sheet and PET-tipped AL1N30 were laminated so that the resin composition layer of the sealing sheet was in contact with Toyo Aluminum's "PET-tipped AL1N30", and then the second sheet of the sealing sheet was peeled off, and the sealing sheet and the glass substrate were laminated so that the resin composition layer was in contact with the Ca film, thereby sealing the Ca film and obtaining a laminated product. These laminations were performed using a roll laminator (Fujipla's "LPD2325", roll material: rubber) under conditions of roll temperature: 90°C, roll speed: 360 mm / min, roll pressure: 0.2 MPa, and nitrogen atmosphere.

[0146] The laminate obtained as described above was placed in an accelerated test machine (Espec Corp.'s "Small Environmental Test Machine SH-222"), and an accelerated test was performed in which the laminate was left for 24 hours under conditions of a temperature of 85°C and a humidity of 85% RH, and the deterioration behavior of the Ca film surface due to the reaction Ca (opaque) + 2H2O → Ca(OH)2 (transparent) was evaluated. Specifically, the reflectance D before the accelerated test and the reflectance E after the accelerated test at 850 nm were measured, and the ratio of the reflectance E after the accelerated test to the reflectance D before the accelerated test (i.e., reflectance E after the accelerated test / reflectance D before the accelerated test, hereinafter sometimes referred to as "E / D") was calculated and evaluated according to the following criterion 3. Note that the higher the E / D, the better the sealing performance of the sealing sheet is judged to be. The results are shown in Table 4 below. (Criterion 3) ○ (Good): E / D is 0.85 or more △(Acceptable): E / D is 0.50 or more and less than 0.85 × (defective): E / D is less than 0.50

[0147] [Table 4]

[0148] As shown by the results in Table 4, the sealing sheet of Comparative Example 1 having a laminated structure of moisture-proof sheet (first sheet) / resin composition layer / moisture-proof sheet (second sheet) can suppress the increase in the moisture content in the resin composition layer during storage, but cannot efficiently dry the resin composition layer. Also, the sealing sheet of Comparative Example 2 having a laminated structure of moisture-proof sheet (first sheet) / resin composition layer / non-moisture-proof sheet (second sheet) cannot suppress the increase in the moisture content in the resin composition layer during storage, and the moisture content after drying is also high. On the other hand, the sealing sheets of Examples 1 and 2 having a laminated structure of moisture-proof sheet (first sheet) / resin composition layer / non-moisture-proof sheet (second sheet) / peelable moisture-proof sheet (third sheet) can suppress the increase in the moisture content of the resin composition layer during storage, and can efficiently dry the resin composition layer while suppressing contamination of the resin composition layer by peeling off and drying the third sheet. [Industrial Applicability]

[0149] The encapsulating sheet of the present invention is useful for encapsulating electronic devices that are sensitive to moisture.

[0150] This application is based on Patent Application No. 2019-205828 filed in Japan, the contents of which are incorporated in their entirety herein.

Claims

1. A sheet for sealing having a laminated structure including a first sheet, a resin composition layer, a second sheet, and a third sheet in this order, The water vapor permeability of the first sheet and the third sheet is independently 5 (g / m 2 / 24hr) or less, The water vapor permeability of the second sheet is 10 (g / m 2 / 24hr) or more, the third sheet is a sheet having an adhesive layer, and the adhesive layer is in contact with the second sheet; and The sealing sheet from which the third sheet can be peeled off.

2. The sealing sheet according to claim 1, wherein a 90-degree peel strength between the second sheet and the third sheet is 0.1 gf / inch or more and 250 gf / inch or less.

3. The encapsulating sheet according to claim 1 or 2, wherein the second sheet has a release layer, and the release layer is in contact with the resin composition layer.

4. The sealing sheet according to any one of claims 1 to 3, wherein the first sheet is a sheet having a release layer, and the release layer is in contact with the resin composition layer.

5. The sealing sheet according to any one of claims 1 to 4, wherein the resin composition layer contains semi-calcined hydrotalcite.

6. The encapsulating sheet according to any one of claims 1 to 5, which is a sheet used for encapsulating an electronic device.

7. The encapsulating sheet according to claim 6, wherein the electronic device is an organic EL device, a quantum dot device, or a solar cell.

Citation Information

Patent Citations

  • Gas barrier film and transfer method of gas barrier film

    JP2017043060A

  • Production method of gas barrier film

    JP2017043062A

  • Water vapor barrier laminate and organic electroluminescent element

    JP2018065328A

  • Sealing sheet

    WO2018181426A1